Evaluation of Die Swell Behavior During Capillary Extrusion of Poly(lactic acid)/ High density polyethylene Blend Melts - Alzarzouri, Fadi; Fawaz Deri (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Poly lactic acid (PLA) and High density polyethylene (HDPE) have been blended in a Brabender plastograph in the molten state. The melt die swell of the blends has been studied by using a capillary rheometer. Effects of the capillary dimensions, shear stress, shear rate, temperature and blending ratio on die swell of PLA/HDPE blend melts were investigated. The results showed that die swell ratio decreased with increasing of capillary length and temperature while it increased with increasing of shear stress, shear rate and capillary diameter. It was also found that the plots of die swell versus blending ratio go through a maximum for blending ratio PLA/HDPE (60/40).